Among ghosts and tigers: The Chinese in the Russian Far East, 1917-1920 - Lin, Y (2015)
This thesis examines the experiences of the overseas Chinese in the Russian Far East during the revolutionary and Civil War period from 1917 to 1920, as well as their responses to the upheaval. Bucking the current trend towards transcultural history, the thesis argues that Chinese identity and nationalist language were of prime importance to this community. By concentrating on Chinese-language sources, the thesis re-privileges the community's internal discourses and highlights the prevalence of nationalist rhetoric across the Sino-Russian border. It also sites the Chinese community's use of nationalist language within the context of the global diaspora, for which questions of national weakness and revival were also pressing. Going further, the thesis postulates the presence of "Chinese nationalism with Russian characteristics", in which the issues surrounding Chinese nationalism as a whole were heightened. It shows that the rhetoric of “national humiliation" and victimhood were particularly immediate to the community in the Russian Far East, since it was located at one of the epicentres of imperial contestation. In practice, this led to a modus vivendi with the Reds and a decisive turn against the Whites. Furthermore, the chaos of the revolutions and Civil War imbued this nationalism with an opportunistic quality. The collapse of Russian state power became the "opportunity of a thousand years" for China to redress past wrongs. This allowed the overseas community to work closely with local authorities and the Beijing government to achieve shared goals. New civil society organisations with community-wide aims were formed. Beijing extended its diplomatic reach in the form of new Far Eastern consulates. Finally, common nationalist rhetoric underpinned China's successful attempt to re-establish its civilian and military presence on the Amur River. "Chinese nationalism with Russian characteristics" could be effectively harnessed to secure multi-level and cross-border cooperation.